Intraoperative fluorescence angiography and risk factors of anastomotic leakage in mini-invasive low rectal resections - Benčurik, Vladimír; Škrovina, Matej; Martínek, Lubomír; Bartoš, Jiří; Macháčková, Mária; Dosoudil, Michal; Štěpánová, Erika; Přibylová, Lenka; Briš, Radim; Vomáčková, Katherine (Surgical endoscopy, 2021)
BACKGROUND: One of the prerequisites for proper healing of the anastomosis after a colorectal resection is adequate blood supply to the connected intestinal segments. It has been proposed that adequate visualization of the blood flow using indocyanine green (ICG) could lead to the reduction in the incidence of anastomotic leakage (AL). The aim of this study was to assess the effectiveness of intraoperative fluorescence angiography (FA) in decreasing the incidence of AL after minimally invasive low anterior resection (LAR) with total mesorectal excision (TME) in rectal cancer patients and to determine predictors of anastomotic leak. METHODS: From August 2015 to January 2019, data from 100 patients who underwent mini-invasive TME for rectal cancer using FA with indocyanine green (ICG) were prospectively collected and analyzed. They were compared with retrospectively analyzed data from a historical control group operated by one team of surgeons before the introduction of FA from November 2012 to August 2015 (100 patients). All patients from both groups were operated sequentially in one oncological center in Nový Jičín. RESULTS: The incidence of AL was significantly lower in the ICG group (19% vs. 9%, p = 0.042, χ2 test). In fifteen patients in the ICG group (15%), the resection line was moved due to insufficient perfusion. Using Pearson's χ2 test, diabetes (p = 0.036) and application of a transanal drain (NoCoil) (p = 0.032) were identified as other risk factors (RFs) for AL. CONCLUSION: The use of ICG to visualize tissue perfusion in low rectal resections for cancer can lead to a reduction of AL.
Keywords: rizikové faktory; Proctectomy; netěsnost anastomózy; Risk Factors; lidé; indokyanová zeleň; nádory rekta; retrospektivní studie; Rectal Neoplasms; anastomóza chirurgická; Anastomotic Leak; Indocyanine Green; proktektomie; fluoresceinová angiografie; Anastomosis, Surgical; Retrospective Studies; Fluorescein Angiography; Humans